2003
DOI: 10.4315/0362-028x-66.5.878
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Ostrich Carcasses Produced at an Export-Approved South African Abattoir

Abstract: The aim of this study was to evaluate the microbial quality of ostrich carcasses produced in a South African export-approved ostrich abattoir. Ninety surface samples were collected from 30 ostrich carcasses at three processing points in the abattoir: after skinning, after evisceration, and after chilling. Samples were evaluated for aerobic plate counts, for levels of Pseudomonas spp., Enterobacteriaceae, and Staphylococcus aureus, and for the presence of Escherichia coli. Surface counts (means +/- standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…As the other types of meat of slaughtered animals, the ostrich meat couldn´t be completely sterile after the cutting carcasses. After skinning, the ostrich meat is exposed to microbial contaminations which may come from a variety of external sources including the hands of workers (Karama, 2001;Hoffman, 2005Hoffman, , 2008. Using the appropriate method of packaging and storage conditions, we can greatly affect the microbial quality of post-mortem and also the durability of ostrich meat.…”
Section: Introductionmentioning
confidence: 99%
“…As the other types of meat of slaughtered animals, the ostrich meat couldn´t be completely sterile after the cutting carcasses. After skinning, the ostrich meat is exposed to microbial contaminations which may come from a variety of external sources including the hands of workers (Karama, 2001;Hoffman, 2005Hoffman, , 2008. Using the appropriate method of packaging and storage conditions, we can greatly affect the microbial quality of post-mortem and also the durability of ostrich meat.…”
Section: Introductionmentioning
confidence: 99%
“…was reported to cause mortality in ostrich chicks (Shivaprasad, 1993;Verwoerd, 2000). However, it was reported that immunosuppressed adult ostriches may shed Salmonella spp., contributing to contamination of products during slaughtering process (Karama et al, 2003). Now a day's antimicrobial resistance that's occurs for microbes of animal origin, including food-producing animals, pet and companion animals, fish and other aquatic animals as well as wild animals, has gained particular attention (Schwarz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, they were not described in these studies (Gopo and Banda 1997;Ley et al 2001;Karama 2005;Gaedirelwe and Sebunya 2008).…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, other authors reported high prevalence of Salmonella spp. in ostrich flocks slaughtered in commercial slaughter-houses (Gopo and Banda 1997;Karama 2005;Gaedirelwe and Sebunya 2008). It is believed that information about farming systems, sanitary management and slaughtering procedures of these ratites could explain the differences in Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation